Removal of an infant's gastric duplication cyst through endoscopic submucosal dissection: A case report. Issue 12 (March 2019) - Fang, Ying; Gao, Tianjiao; Yang, Hongbin; Ma, Shiyang; Li, Quanlin; Zhou, Ping-Hong
Abstract: Rationale: Gastric duplication cyst is an anomaly that primarily occurs to children. Apart from the conventional use of surgical resection, few cases using endoscopic treatment have been reported. Patient concerns: A 5-month-old female infant was hospitalized with the chief complaint of gastric cyst. No significant abnormalities were identified by physical examination. Interventions: Endoscopic submucosal dissection (ESD) was performed successfully for the infant and the duration was less than 20 minutes. The patient showed no postoperative complications. Outcomes: At 4 months during the follow-up, upper endoscopy revealed a small scar at the previous site of the lesion and no recurrence. Lessons: According to the results of PUBMED review, she was the youngest with gastric duplication cyst removed with ESD. The less invasive ESD should be considered an effective therapeutic option to remove gastric duplication cyst in children.